“A call to action: amplifying the role of men in bridging the gender gap in live kidney donations"- A Letter to the Editor - Kamran, Tafiya Erum; Inam, Rida; Haider, Zaira (Journal of the Pakistan Medical Association, 2024)
Dear Editor, We are writing this letter to expound upon an underreported and rarely talked about issue referencing the gender bias invloving the live kidney donations. That being said, the purpose of this letter is purely to underscore the fact that women are less likely to receive a living donor transplant as compared to men. However, they are more likely to serve as living donors for kidney transplantation. [1] Multiple contributory factors including societal stigmas and cultural biases can be attributed to this approach. The evidence of this sex disparity is much more prominent in south Asian countries where men have a 10 times more likely chance to receive a kidney transplant than women. [2] Apart from the male dominance influenced by the socioeconomic reason, this gender imbalance is difficult to quantify. Many women feel obliged to accept the traditional role to care for sick family members. They are less able to refuse the appeal for help within the family compared to men. This is especially true for mothers and spouses. [3] When it comes to men, documented instance in literature show that men in situations where they needed to donate silently disappear from the scene and only show up once the transplantation is over, leaving the women to step forward in this situation. This, cowardice of men is cemented by a recent story of a 36-year-old man with end- stage renal failure. Although one of his healthy brothers was a perfect match, the burden of the transplant still befelled on their old mother. [4] Kidney donation is an act of altruism and devotion. As evidenced by the statistics, the local literature also have frequently portray that women are the frontrunners in this race, while the men are falling far behind. Here the authors need to make it very clear that our purpose is not to say that all men would react this way, but it is to highlight the huge contrast between men and women stepping up as donors for their families. The primary objective of this letter is to accentuate the importance of enhanced access to care for women requiring transplantation while fostering within the male population a deeper understanding of the myths surrounding organ donation and the vital importance of supporting the women in their lives during such critical moments.